Water pollution and habitat degradation in the Gulf of Thailand - Voravit, Cheevaporn (ScienceDirect, 2016)
The Gulf of Thailand has been a major marine resource for Thai people for a long time. However, recent industrialization and community development have exerted considerable stress on the marine environments and provoked habitat degradation. The following pollution problems in the Gulf have been prioritized and are discussed in details: (1) Untreated municipal and industrial waste water are considered to be the most serious problems of the country due to limited waste water treatment facilities in the area. (2) Eutrophication is an emerging problem in the gulf of Thailand. Fortunately, the major species of phytoplankton that have been reported as the cause of red tide phenomena were non-toxic species such as Noctiluca sp. and Trichodesmium sp. (3) Few problems have been documented from trace metals contamination in the Gulf of Thailand and public health threat from seafood contamination does not appear to be significant yet. (4) Petroleum hydrocarbon residue contamination is not a problem, although a few spills from small oil tankers have been recorded. A rapid decrease in mangrove forest, coral reefs, and fisheries resources due to mismanagement is also discussed.